“Life of Constantine” by Eusebius of Caesarea as “sacred history”: a typology of Moses — Constantine - Maksim Prikhodko (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
In the article, the conceptual model of the holy emperor in one of the first monuments of Christian hagiographic literature, “Life Constantine” by Eusebius of Caesarea, is investigated. The analysis is based on the typological comparison of Emperor Constantine with the biblical figure of Moses, conducted by Eusebius. As part of this comparison, the development of a “sacred image” in history is traced, which forms a kind of “sacred history” beyond the biblical framework. Philo of Alexandria’s view of the unity of the laws of nature and the written legislation of Moses as having a single source - the Logos of God, Eusebius extends to the conformity of the biblical character and the contemporary historical figure of the emperor. Following the Logos, Constantine performs the same pattern Moses fulfilled in his life. In the development of the typological line of Moses-Constantine, three moments of the formation of the figure of Constantine in sacred history are traced: receiving the kingdom, accepting the ministry of the priesthood, and gaining the gift of prophecy. The descriptive convergence of the biblical story and modern (to the author) history means not so much the dependence of one narrative on the other but their general dependence on the Logos acting in history as the Law of nature, which guides the course of history and shapes its events. Eusebius reflects in the biography of the emperor the Principle, which equally acts both in the sacred events of the history of Moses and in the relatively recent events for Eusebius Constantine. In this single Beginning, the biblical story, perceived “by ear” and therefore having the “look of a myth”, acquires visible features, and current reality is endowed with the meaning of the sacred biblical story. The “Life of Constantine” thus demonstrates the mechanism of fixation in the memory of sacred events that make up a particular, sacred line of history.